2020
DOI: 10.1088/1361-6404/ab805c
|View full text |Cite
|
Sign up to set email alerts
|

Item response curve analysis of Likert scale on learning attitudes towards physics

Abstract: The item response curve (IRC) shows the proportion of item responses plotted against total scores achieved in an assessment instrument. It has acquired widespread employment in the field of physics education to analyze tests on physics content knowledge. In the current study, the IRC was lengthened to investigate attitude items of Colorado Learning Attitudes about Science Survey (CLASS) with a five-point Likert rating format. How well the IRC explained polytomous data and its advantages were considered. Collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Gray et al found that students were least successful at identifying "physicist" responses for these two items, and that item 12 had the lowest consistency among experts [4]. Reyes and Rakkapao removed item 8 from their Item Response Curve analysis; 75% of students in their sample chose the non-expert-like response, and an expert-like response on this item correlated with less expert-like attitudes overall [21].…”
Section: B Irt Resultsmentioning
confidence: 99%
“…Gray et al found that students were least successful at identifying "physicist" responses for these two items, and that item 12 had the lowest consistency among experts [4]. Reyes and Rakkapao removed item 8 from their Item Response Curve analysis; 75% of students in their sample chose the non-expert-like response, and an expert-like response on this item correlated with less expert-like attitudes overall [21].…”
Section: B Irt Resultsmentioning
confidence: 99%
“…The technique also enables educators able to recognize that some correct answers are better than others. This is a very useful technique and has been used for analysing concept items for different CIs used in introductory physics, in different culture, language and educational systems (Ishimoto et al, 2017;Mashood, 2014;Morris et al, 2006;Morris et al 2012;Rakkapao et al, 2016;Reyes & Rakkapao, 2020;Richardson et al, 2021). This study also utilised the item analysis method.…”
Section: The Item Response Curvesmentioning
confidence: 99%
“…There has been much discussion of whether or how to quantify and summarize Likert scale data [22,23]. Given the preliminary nature of this paper, we take the admittedly simplistic approach of simply stating the percentage of students who choose "Agree" or "Strongly Agree" for each question.…”
Section: B Students' Attitudesmentioning
confidence: 99%